Estudio de riesgo vocal ergonómico y disfonía ocupacional en la gestión del aula en docentes de la Unidad Educativa MARTIM CERERÊ 2015. Programa de prevención de riesgos. - Fuertes Morillo, Fausto Artemio (2016)
This work was carried out at the Martim Cererê Bilingual Private Educational Unit, an institution of recognized prestige for the training of students with high values and knowledge. The problem of the research dealt with was related to the presence of vocal affections in the teachers of the educational unit and the consequences that it is causing in their health.